"Where does it come from?": A call for explicating implicit theories of interpretive and supervisory techniques in psychoanalytic supervision*. (2nd January 2021) - Töpfer, Nils F.
Abstract: The knowledge culture of psychoanalysis relies heavily on the practical wisdom of competent psychoanalytic clinicians. In order to become competent analysts, analysts in training should not content themselves with trusting in their supervisors' intuition and expertise. There is a need for supervisors and supervisees to explicate implicit theories of interpretive and supervisory techniques in psychoanalytic supervision by raising the question "Where does it come from?" with regard to three too often neglected issues. First, both the supervisor and the analyst in training should actively and constantly try to make transparent the process of contextualization, that is, the methodology of inferring latent meaning from manifest content through privileging certain pieces of information over others. Second, it should become an ongoing task in supervision that concrete (recommendations about) technical interventions are embedded in and reflect the application of a particular theory of technique. This facilitates an understanding that goes beyond the interpretation in a concrete situation and helps to generalize learning into a gradually expanding, integrated technical framework. Third, we should reflect and explicate the (predominant) supervisory approaches we are using in order to remain flexible with regard to both supervisory material and ways of reacting to it. Discussing these issues will enable analysts in training to develop their own psychoanalytic identity and integrated frame of reference for their practice that they critically and deliberately reflect upon and actively acquire rather than passively and seemingly intuitively absorb and adopt. Examples for illustrating the explication of theories of interpretive and supervisory techniques are provided.